Status of woolly aphid Ceratovacuna lanigera and establishment of the parasitoid Encarsia flavoscutellum in sugarcane germplasm - Jandhyala, Srikanth; Mahendran, B; Singaravelu, B; Mahesh, P; Salin, K.P; Chandran, K (Journal of Sugarcane Research, 2021)
Woolly aphid Ceratovacuna lanigera Zehntner (Hemiptera: Aphididae), a native of north-eastern India, appeared in the world sugarcane germplasm maintained at the ICAR-Sugarcane Breeding Institute Research Center (ICAR-SBIRC), Kannur, Kerala State, India, first in 2004. The aphid colonized Indian hybrids and accessions of Saccharum officinarum, Saccharum sinense, Saccharum robustum and Saccharum barberi in the first year of occurrence and every year thereafter. Early detection and spot application of insecticide were adopted to manage the aphid and protect germplasm. Soap solution was applied in the later years to conserve the predators Dipha aphidivora Metrics (Lepidoptera:Pyralidae) and Micromus sp. (Neuroptera: Hemerobiidae) that occurred intermittently. The parasitoid Encarsia flavoscutellum Zehntner (Hymenoptera: Aphelenidae) maintained at Coimbatore, Tamil Nadu State, India, was released in the germplasm thrice, i.e. in January 2009, November 2014 and June 2015. Post-release, E. flavoscutellum parasitism was detected first during April-June 2015 at low levels (2.0- 3.5%). Clear-cut evidence of establishment was witnessed during September-October 2021 when aphids showed a high 27.0% parasitism. Since E. flavoscutellum was found to regulate populations of woolly aphid wherever it established, it is expected to reach similar equilibrium with the aphid in the germplasm, D. aphidivora and Micromus sp. playing a complementary role at high aphid densities. However, continuous monitoring of aphid and natural enemies, and use of safer emergency control measures would go a long way in maintaining the germplasm free from woolly aphid.